FRI0307 DETERMINANTS OF PATIENT-PHYSICIAN DISCORDANCE IN GLOBAL ASSESSMENT IN SPONDYLOARTHRITIS. (2nd June 2020) - Azevedo, S.; Guimarães, F.; Almeida, D.; Faria, D.; Silva, J.; Rodrigues, J.; Peixoto, D.; Alcino, S.; Tavares-Costa, J.; Afonso, C.; Teixeira, F.
Abstract : Background: Patient's Global Assessment of Disease Activity (PtGA) and Physician's Global Assessment of Disease Activity (PhGA) are important measures in the evaluation of patients with Spondyloarthritis (SpA), but often provide discordant results. 1 Both PtGA and PhGA are assessed as part of ankylosing spondylitis disease activity score (ASDAS), that is a measure of axial SpA disease activity endorsed by the Assessment of SpA International Society (ASAS) and Outcome Measures in Rheumatology. 2, 3 In peripheral SpA, although there are no formally validated indexes, the American College of Rheumatology (ACR) and Disease Activity Score 28 (DAS 28) response criteria have shown reliable discriminant characteristics and both include PtGA and PhGA. 3 The lack of concordance between PtGA and PhGA may mislead treatment decisions, namely switches. Objectives: To assess the determinants of patient-physician discordance in SpA patients under biologic treatment. Methods: Cross-sectional study, including 72 with SpA according ASAS criteria. Physicians' evaluation included comorbidities, parameters of inflammatory activity (erythrocyte sedimentation rate [ESR] and C-reactive protein [CRP], PhGA, ASDAS PCR and, DAS 28, and Participants completed patient-reported outcomes (PROs) and sociodemographic characteristics. For statistical analysis, SPSS was used and significance level was 2-sided p<0.05. Results: Clinical and laboratory characteristics of patients are shown in table 1. PtGA and PhGA were significantly different (34.8±21.2 vs 7.8±12.5 mm, respectively, p< .001) and patient-physician discordance (ΔPtGA - PhGA) was 27.5±14.3 mm. In peripheral SpA, patient-physician discordance had a correlation with patient age, Health Assessment Questionnaire (HAQ), Functional Assessment of Chronic Illness Therapy (FACIT), EuroQol-5 dimension (EQ5D), Short Form (36) Health Survey (SF-36), Hospital Anxiety and Depression scales (HADS), CRP, ESR, number of comorbidities and daily medication, and an association with employment status (employees had lesser discordance), anxiety/depression, fibromyalgia and osteoarthritis (OA). In multivariable analysis including employment status, SF-36, OA, number of comorbidities, and ESR (R 2 adjusted= .505), the main predictors of patient-physician discordance were lower SF36, higher number of comorbidities and employment status. In axial SpA, patient-physician discordance had a correlation with nocturnal back pain and total back pain VAS, FACIT, EQ5D, SF-36, HADS, Bath Ankylosing Spondylitis Functional Index (BASFI) and Bath Ankylosing Spondylitis Activity Index (BASDAI) scales, age, number of comorbidities and daily medication and an association with employment status (employees had lesser discordance), anxiety/depression and fibromyalgia. In multivariable analysis including employment status, SF-36, fibromyalgia, and number of comorbidities (R 2 adjusted= .738), the main predictors of patient-physician discordance were lower SF36, higher number of comorbidities and concomitant diagnosis of fibromyalgia. Neither for peripheral SpA nor for axial SpA an association with SpA subtype, HLA-B27 positivity, patient or physician gender, or patient education level was found. Conclusion: This study shows the variability implied in patient-physician discordance. We have demonstrated that comorbidities, employment status, and other factors not directly related to the disease are determinants for the patient-physician discordance. References: [1]Desthieux C, et al. 2016 [2]Machado P et al. 2013 [3]Mease PJ. 2011 Disclosure of Interests: None declared